Coagulation activation in sickle cell trait: an exploratory study. (7th September 2015) - Amin, Chirag; Adam, Soheir; Mooberry, Micah J.; Kutlar, Abdullah; Kutlar, Ferdane; Esserman, Denise; Brittain, Julia E.; Ataga, Kenneth I.; Chang, Jen‐Yea; Wolberg, Alisa S.; Key, Nigel S.
Summary: Recent epidemiologic data suggest that sickle cell trait (HbAS; AS) is a risk factor for venous thromboembolism. We conducted an exploratory study of healthy subjects with AS under baseline conditions to determine whether a chronic basal hyperactivation of coagulation exists, and if so, what mechanism(s) contribute to this state. Eighteen healthy AS individuals were compared to 22 African‐American controls with a normal haemoglobin profile (HbAA; AA) and 17 patients with sickle cell disease (HbSS; SS). Plasma thrombin‐antithrombin complexes and D‐dimer levels were elevated in AS relative to AA patients ( P  = 0·0385 and P  = 0·017, respectively), and as expected, were much higher in SS versus AA ( P  < 0·0001 for both). Thrombin generation in platelet poor plasma was indistinguishable between AA and AS subjects, whereas a paradoxical decrease in endogenous thrombin potential was observed in SS ( P  ≤ 0·0001). Whole blood tissue factor was elevated in SS compared to AA ( P  = 0·005), but did not differ between AA and AS. Plasma microparticle tissue factor activity was non‐significantly elevated in AS ( P  = 0·051), but was clearly elevated in SS patients ( P  = 0·004) when compared to AA controls. Further studies in larger cohorts of subjects with sickle cell trait are needed to confirm the results of this preliminary investigation.